DAYA HIDUP DAN INTENSITAS SERANGAN BUBUK KAYU KERING HETEROBOSTRYCHUS AEQUALIS WAT PADA KAYU PULAI (ALSTONIA SCHOLARIS R.Br) - Ginuk Sumarni; Jasni Jasni (Pusat Penelitian dan Pengembangan Hasil Hutan, 1988)
In Indonesia Heterobostrychus aequalis Wat is a large size powder post beetle. This species very commonly attacks highly stachy wood, the main reason why they are used in this experiment.In this research pulai wood (Alstonia scholaris R.Br) has been used for sample, dried at temperature levels for 40°C, 60oC, 90oC, 100oC, 120oC, 150oC, 200oC and ambien air temperature. On each side of wood samples ten holes were made with dimension of 1,5 cm x 5 cm x 7 cm. Into the hole larvaes of 1,5 month old were placed. The observations were made after six week period.The result showed that wood dried on temperature 40°C could reduce the starch of about 9,08% so that intensity of insect's attack were lower (score 44,2). High starch content was found in the wood dried at temperature 200°C, that is 17,94%. In this sample the intensity of the attack was higher, that scale at scoring.